Synthesis, characterization and antibacterial activity of bis thiourea derivatives - Jayakumar, Ponniasalan (Universiti Malaysia Sarawak (UNIMAS), 2015)
A series of bisthiourea derivatives were succesfully synthesized by reaction of benzene-1, 4 dicarbonyl isothiocyanate intermediates and isophthaloyl dichloride, with a series of aromatic amine at ortho, meta and para position. The structure of synthesised compound characterized by infra-red spectroscopy (FTIR), 1H Nuclear magnetic resonances, and 13C Nuclear magnetic resonances. The synthesised compounds were screened for their antibacterial properties using Gram-negative bacteria Escherichia coli (E.coli) by using disc diffusion method. All of synthesized series showed negative results towards antibacterial activity.